Business Ethics and Integrity a Case Study on 300 U.S. Listed Companies - Tinjala, Diana Maria; Pantea, Lavinia Mirela; Buglea, Alexandru (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
Profit-maximizing behavior or moral integrity? Can companies have both? Our study takes a look at 300 U.S. based companies listed on the New York Stock Exchange and NASDAQ, and their way of dealing with business ethics. The research undertaken focuses on the content analysis method, using the corporate Codes of conduct and Corporate Social Responsibility (CSR) reports. The study reveals the evolution of the corporate ethics policies and programs throughout the years 2010- 2014. We also take a look at the most frequent controversies concerning business integrity, by sectors of activity.